Parameters affecting the adsorption of copper (II) and lead (II) from Aqueous Solution by oil palm shell in batch adsorption system - Chong, Harry Lye Hin (Universiti Malaysia Sabah, 2013)
The aims of this work were to: (i) determine the suitability of oil palm shell as constructed wetland filter bed media by analyzing its particle size distribution, (ii) investigate the physico-chemistry properties of oil palm shell, and (iii) study its heavy metal adsorption by using Cu(II) and Pb(II) as model heavy metal which include studies on the: (a) effect of various selected parameters on the adsorption performance, (b) theoretical monolayer adsorption capacity, and (c) adsorption kinetic and mechanism. All the methods used were standard and established. The oil palm shell was found to be suitable for constructed wetland application based on its particle size distribution and characterization studies. The effect of various parameters on the Cu-{)PS and Pb-OPS adsorption performance followed typical findings. The theoretical monolayer adsorption capacities of OPS towards Cu(II) and Pb(II) were 1.76 and 3.39 mg/g, respectively. The compliance with various kinetic models, namely, intraparticle diffusion model, expression of Boyd and pseudo-second-order modeJ, indicated that various adsorption mechanisms were involved. The adsorption process is believed to have started from bulk diffusion followed by combination of film and intraparticle diffUSions, and ended with adsorption on binding sites which was probably chemisorption.